Static and Dynamic Aspects of Application Domains: An Inductively Defined Modeling Technique That Allows Decomposition - Theo van der Weide; Fiona Penlope Tulinayo; Patrick van Bommel (Complex Systems Informatics and Modeling Quarterly)
Modeling is one of the most important parts of requirements engineering. Most modeling techniques focus primarily on their pragmatics and pay less attention to their syntax and semantics. Different modeling techniques describe different aspects, for example, Object-Role Modeling (ORM) describes underlying concepts and their relations while System Dynamics (SD) focuses on the dynamic behavior of relevant objects in the underlying application domain. In this paper we provide an inductive definition for a generic modeling technique. Not only do we describe the underlying data structure, we also show how states can be introduced for relevant concepts and how their life cycles can be modeled in terms of System Dynamics. We also show how decomposition can be applied to master complex application domains. As a result we get an integrated modeling technique covering both static and dynamic aspects of application domains. The inductive definition of this integrated modeling technique will facilitate the implementation of supporting tools for practitioners.